Morphological and Productive Correlations of Cutting Pennisetum Varieties Under Conditions of Peruvian Humid Tropics - Pinchi-Carbajal, S. F.; Quispe-Ccasa, H. A.; Ampuero-Trigoso, G.; Nolasco-Lozano, E.; Saucedo-Uriarte, J. A. (Tropical Animal Science Journal, 2024)
Livestock farming in the Peruvian tropics is based on the use of grazing forage, but cutting grasses offers greater productivity and seasonality advantages. In this study, the morphological and productive characteristics of King Grass Morado (KGM), Cuba OM-22 (CU), and Maralfalfa (MA) were evaluated and correlated with chlorophyll content under Peruvian humid tropic conditions. Five plots of 1 ha each were installed for the three Pennisetum varieties (2-1-2), with three samples per plot. No significant differences were found in plant height, leaf length, number of nodes, number of leaves/stem, number of stems, stem circumference, length of nodes, leaf, stems, and total weight, chlorophyll index (atLEAF CLOR), performance index (API), and dry matter. KGM stood out in tillering (12.86) (p<0.01), but CU and MA showed greater leaf width (4.16 and 4.42 cm, respectively) (p<0.05). The calculated biomass production was 40.3 t/ha for KGM, 24.5 t/ha for MA, and 76.5 t/ha for CU. MA had higher nitrogen (0.70%) and protein (4.33%) contents (p<0.01). The correlations were significant between stem height with the number of nodes and leaf width, stem circumference with stem, leaf, and total weight (p<0.05), and nitrogen and protein content were estimated with the atLEAF CLOR and API values of the basal leaves with R2 = 0.548 and R2 = 0.563, respectively (p<0.05). In conclusion, KGM, CU, and MA differed in some morphological and productive variables and were correlated with others; furthermore, the protein content could be estimated with the atLEAF CLOR and API values in these Pennisetum varieties.